(untitled) (Revista de Artes Marciales Asiáticas, 2023)
This report describes the 7th European Judo Science & Research Symposium & 6th Scientific and Professional Conference - "Applicable research in judo" held in Poreč, Croatia on June 19-20, 2023. The two-day conference included three keynote speakers on the first day and 20 oral presentations divided into two sections. The second day included four practical sessions, which closed the program. The conference proceedings book was published, which includes 24 papers. The conference was again impeccably organised and had an outstanding return after the Covid-19 interruption, with many exciting topics presented by researchers and judo practitioners. Additionally, slightly more judo coaches and ex-athletes joined the conference, bringing us one step closer to tightening the gap between judo science and coaching.